Capital income taxation and risk-taking in a small open economy - Asea, Patrick K.; Turnovsky, Stephen J. 1941- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1997)
How do capital income taxes affect household portfolio choice and growth? We" approach this question within the context of a stochastic model of a small open economy in" which taxes on income from domestic capital (equity) and foreign bonds affect household" portfolio choice, welfare and the growth rate of the economy. The theoretical and numerical" analysis demonstrates the important role that risk plays in determining the mean and variability" of growth as well as the conditions under which a higher tax rate can be welfare improving. To" shed more light on the complex theoretical interaction between taxes and risk-taking we estimate" a reduced-form multinomial probit model of household portfolio choice using the method of" simulated moments. The empirical evidence is in stark contrast to the conventional wisdom " we find that higher taxes make it less likely that the household will hold risky assets."